The Randomized Branch Sampling - A Cost Effective Estimation Method of above Ground Biomass - Chhetri, Purna B.; Katwal, Santosh; Dukpa, Tashi; Drukgyel, Sonam; Gregoire, Timothy G. (Indian Forester, 2016)
Forest ecosystem plays an important role in global cycling and storing and United Nations Framework Convention on Climate Change (UNFCC) and its Kyoto Protocol recognized the role of forests in carbon sequestration and storage. Modelling forest dynamics, predicting future yield, and exploring alternatives sustainable management options require accurate tree wood volume and biomass estimation. In order to achieve best biomass estimation, it is important to use appropriate biomass sampling technique that is unbiased. Here we described a randomized branch sampling a technique recently been popularized in forestry to sample above ground biomass of tree species (Gregoire et al.,1995) in relatively most cost effectiveand statistically reliable manner.